Genome-wide identification of MYBL2 in Brassicaceae, with a focus on the expression pattern of regulating anthocyanin synthesis in Brassica crops - Wang, Chenchen; Zhang, Qi; Liu, Yi; Shen, Wenjie; Wan, Shubei; Chen, Lunlin; Tan, Chen; Chen, Daozong (Frontiers in Plant Science, 2025)
The Brassicaceae family includes the model plant Arabidopsis thaliana, along with various vegetables and oil crops, which possess significant economic and scientific value. Notably, three diploid species within the U’s Triangle of Brassica have undergone natural hybridization, resulting in the formation of three allotetraploid species, which provides an excellent model for investigating the phylogenetic, evolutionary, and functional differentiation of plant homologous genes. In this study, we systematically identified MYBL2 homologous genes within the 31 Brassicaceae species, with a total of 48 homologous genes identified from 30 species, and phylogenetic analysis revealed the presence of six subfamilies, Ka/Ks analysis showed that only 10 MYBL2 homologous gene were positively selected during evolution. We subsequently concentrated on the evolution, gene structure, and conserved domain analysis of 16 MYBL2 homologous genes across six Brassica crops found in U’s Triangle. Our findings indicated that these 16 MYBL2 homologous genes predominantly clustered into two branches and exhibited a high degree of evolutionary conservation. Further RNA-seq analysis of various tissues and organs from Brassica crops demonstrated that MYBL2 homologous genes were significantly up-regulated in tissues with anthocyanin accumulation. Concurrently, we employed Weighted Gene Co-expression Network Analysis (WGCNA) to identify hub genes regulated by anthocyanin in different tissues of B. napus, revealing that BnaMYBL2.C06 exhibited a strong repressor with anthocyanin biosynthetic genes (ABGs) in petals. Finally, quantitative reverse transcription PCR (qRT-PCR) analysis of B. napus leaves, stems, and petals indicated that four MYBL2 homologous genes were significantly up-regulated in leaves and petals, with expression patterns consistent with those of ABGs. Our results contribute new insights into the transcriptional regulatory mechanisms of anthocyanin in Brassica crops.